Local Wisdom Values in Malangan Masked Wayang Art as a Culture of Malang Community - Anik Rofi'atul Mahmudah; Onik Faridah Nikmatullah (Universitas Airlangga, 2026)
Abstract: This study examines the local wisdom values embedded in Malangan Masked Wayang (Wayang Topeng Malangan) as a cultural representation of the Malang community. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving cultural practitioners and community members. The findings reveal that Wayang Topeng Malangan contains multidimensional values, including religious, moral, aesthetic, social, and educational values. These values are reflected in ritual practices, narrative structures, artistic elements, and community participation. The study also highlights that this traditional art functions not only as entertainment but also as a medium for cultural transmission, identity formation, and character education. Furthermore, the integration of local wisdom values in education is considered effective in strengthening cultural awareness and moral development among younger generations. In the context of globalization, Wayang Topeng Malangan plays an important role in preserving local identity and cultural sustainability. Therefore, this art form remains relevant as a cultural asset that supports both social cohesion and educational development. Keywords: local wisdom, Wayang Topeng Malangan, cultural values, character education, cultural preservation